Arithmetic split effect in complex subtractions. Issue 9 (17th June 2015) - Xiang, Yan-hui; Mo, Lei
<x xml:space="preserve">Abstract</x> This study explores the relationship between the split effect and the use of exact versus approximate strategies in complex-subtraction calculations. One-hundred and two-digit subtraction problems were presented, with half of them being small-split problems with answers ±2 or ±5 from 50 and the other half being large-split problems with answers ±10 or ±15 from 50. Participants were asked to indicate whether the answer was less than 50. The measures were speed and accuracy of task performance, and high temporal resolution event-related potentials. Behavioral data showed that participants had a longer time requirement and a lower accuracy in solving small-split problems than in solving large-split problems. Event-related potential data show that, comparatively, the small-split problems led to more-negative, more-lateralized waves as early as 250 ms at frontal, frontocentral, and central sites. Our results, which are in agreement with previous studies, suggest that the participants used exact strategies to solve small-split problems and approximate strategies to solve large-split problems when performing complex subtractions. These results further our understanding of the brain mechanisms underlying the relationship between small/large-split effects and exact/approximate strategies in this task domain.